Basaloid follicular hamartoma: an infrequent entity - Reshma, Tarra; Gopal, K. V. T.; Raju, P. V. Krishnam; Rani, B. Rekha (International Journal of Research in Dermatology, 2024)
Basaloid follicular hamartoma is a rare, benign, skin adnexal tumor. Several clinical patterns have been reported, but they all share the same histopathological features. BFH may be hereditary or nonhereditary and can be accompanied by systemic diseases. Microscopic examination of BFH shows branching cords and anastomosing strands of basaloid cells in a loose, fibrous stroma. The most important pathological differential diagnosis is infundibulocystic basal cell carcinoma. These two lesions must be differentiated carefully based on clinical presentation and histopathological picture, and even molecular studies may be needed. We report a case of 60 year old female who came with a complaint of asymptomatic dark colored raised lesion over right side of face since 2 years. On evaluation lab investigations were found to be normal and histopathological examination showed interanastomosing cords and nests of basaloid cells, few abortive hair papillae and prominent melanophages. Based on these changes patient was diagnosed with basalloid follicular hamartoma and was advised for surgical excision.